Pemilihan Supplier Sodium Hiroxide Liquid Integrasi Dengan Metode AHP – Topsis - Munir, Muhamad (Jurnal Teknik Industri, 2016)
PT. Eterindo Nusa Graha is a company engaged in basic chemical industry that produces synthetic resins and glycerine. One of the raw material for production of synthetic resins is DOP produced 45,000 tons/year. One adjuvant DOP is sodium hydroxide liquid. The raw material is supplied by several companies so that in choosing a major supplier to supply sodium hidroxide is important. Sodium hydroxide liquid supplied by Manunggal indah, Toya indo, and Surya Makmur. In reality the quality of raw materials are sometimes less suitable and delays in delivery have an impact on the production process. So that needs to be measured to determine the supplier's performance. Supplier selection is expected to suit the needs of PT. Eterindo Nusa Graha. This study aims to determine the criteria and sub-criteria supplier selection according to the needs of companies and provides the results of decision-making for the selection of the supplier company. The method used in this study is used AHP weighting of the criteria and sub-criteria and TOPSIS. The results of the research produced 6 criteria and 14 sub-criteria. Of AHP, the weight of the biggest criteria is Quality (0.38651) and Delivery (0.17208), while from TOPSIS method produces major supplier PT. Manunggal indah with positive ideal distance value 0.008558653 and negative ideal distance value 0.04522.